Zdziwienie czy aprobata? Obraz doświadczenia religijnego w powieści Františki Jirousovej Vyhnanci - Gawarecka, Anna (Slavia Occidentalis, 2017)
It is only natural that the rapid secularization of the Czech society has become an object of interest of political scientists, religious and cultural scientists and sociologists. The secularization is sometimes considered a result of dissolution of the traditional models treated as incontrovertible identity based on belief in the existence of the highest instance. It is regarded a donor and guarantee of absolute rights (ontological and ethical) determining the ways in which the anthroposphere operates. This situation often raises concern; on the one hand, it is related to ideological pluralism increasingly hindering the axiological agreement between all members of the society and, on the other hand, it initiates a discussion about the necessity of searching and confirming new identity patterns. Františka Jirousová’s novel Vyhnanci (The Exiles) presents the spiritual indecisions of young people and as such it could be acknowledged as a literary manifesto of this concern. The prestigious Jiří Orten prize awarded to the novel shows that religious and metaphysical questions are still important issues which do not cease to affect the postmodern world.